Vocabulary Learning Strategies in Vocational School for English Specific Purposes - Irawan, Selvia; Ciptaningrum, Dyah Setyowati; Faizal, Abdul Azis (International Journal of Contemporary Studies in Education, 2023)
There are several difficulties for both teachers and students in EFL classrooms while planning lessons and activities. The way they deal with the challenge, the quality with which they perform the task, and the value they provide to the group are just some of the ways in which this circumstance reveals its solutions. In this research, we questioned SMKN 2 Magelang's business and management students to get insight into the challenges they face while trying to learn English. The researchers in this study used a qualitative approach by recording their observations and conducting in-depth interviews. The results were confirmed once the data was summarized and presented. The results show that ESL students experience a broad variety of challenges while learning English. This happened because of the wide range of pupils' starting points in terms of competency.